Direct synthesis of a semiconductive double-helical phosphorus allotrope in a metal-organic framework - Sergei A. Sapchenko; Rodion V. Belosludov; Inigo J. Vitoria-Irezabal; Ivan da Silva; Xi Chen; George F. S. Whitehead; John Maddock; Louise S. Natrajan; Meredydd Kippax-Jones; Dukula De Alwis Jayasinghe; Carlo Bawn; Daniil M. Polyukhov; et al. (Nature Communications, 2025)
Abstract There remains much ambiguity regarding the structure of red phosphorus. We report the adsorption and photo-polymerisation of P4 molecules encapsulated in an indium(III)-based metal-organic framework to afford a double-helical chain composite comprising of [P8] units. The similarity between the Raman spectrum of bulk red phosphorus and of the metal-organic framework – (P8)n adduct suggests the presence of such helical chains in the structure of amorphous red phosphorus. This provides crystallographic evidence of the structural building blocks of the red phosphorus allotrope stabilized within the pores of a metal-organic host. The (P8)n inclusion compound is an air-stable semiconductor with a band gap of 2.3 eV, which is relevant for gas detection and photo-catalysis. We demonstrate that this phosphorus adduct demonstrates a 10-fold increase in conversion in the oxidation of methyl orange dye compared with the parent metal-organic framework material.